Включения в алмазе и алмазоносные породы - Гаранин В. К. Виктор Константинович; Кудрявцева Г. П.; Марфунин А. С. Арнольд Сергеевич; Михайличенко О. А. (Москва, Изд-во МГУ, 1991)
Авт. указаны на обороте тит. л.